Characterization of the antimicrobial substances produced by Nibribacter radioresistens - Kim, Sam Woong; Ha, Yeon Jo; Gal, Sang Wan; Lee, Kyu Pil; Bang, Kyu Ho; Kang, Myung-Suk; Yeo, Joo-Hong; Yang, Hee-Sun; Jeon, Seung-Ho; Bang, Woo Young (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study characterized the antimicrobial substances produced by the radiation-resistant bacterium Nibribacter radioresistens. The antimicrobial substances showed activity against Salmonella Gallinarum, pathogenic Escherichia coli, Bacillus cereus, Streptococcus iniae, and Saccharomyces cerevisiae. The substances showed higher activity against Gram-positive bacteria than against Gram-negative bacteria and yeast. N. radioresistens showed the best growth rate in LB liquid medium at 37ºC; however, production of the antimicrobial substances was not associated with growth. Since the activity of the antimicrobial substances was affected by proteinase K and EDTA, the substances were presumed to be antimicrobial peptides (AMPs). The antimicrobial substances produced by N. radioresistens were unstable at higher temperatures and in acidic and basic pH ranges, and most of the activity was attributed to either low (<3 kDa) or high molecular weight (>30 kDa) molecules. When S. Gallinarum was treated with the antimicrobial substances, the cell destruction was acted on the cell envelope. Therefore, we concluded that N. radioresistens produces broad-spectrum and very unstable antimicrobial substances that mostly consist of low- and high-molecular weight peptides.